La ansiedad como factor causal en el abuso de cannabis - Rosero Bravo, Marybi Jamileth (2019)
The purpose of this case study is to determine the cause of cannabis use in persons deprived of liberty who are not repeat offenders and who suffer from some type of anxiety disorder while being deprived in the Babahoyo Social Rehabilitation Center. The symptoms of anxiety that usually occur in them are: excessive worry, feelings of inadequacy, intense fears that become excessive. The typology of the most notable anxiety disorders in PPL in the Babahoyo CRS is the crisis of anguish, agoraphobia, and substance-induced anxiety disorder. For the collection of patient data the methodology that was used was the psychological interview, observation and application of psychometric tests, tools that helped us to make an adequate psychological assessment and thus determine the causal factor of cannabis abuse in the patient